Translation and validation of Portuguese of a questionnaire for evaluation of psychosomatic symptoms in adults with atopic dermatitis - Manuela Boleira; Omar Lupi; Gisele Vianna Pires; Gabriela Dias; Amanda Jaccobson Seba; Daniel Boleira Sieiro Guimarães (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND: atopic dermatitis is directly related to psychological stress, reduced quality of life and psychosomatic symptoms. The Psychosomatic Scale for Atopic Dermatitis is the only questionnaire developed specifically for assessment of psychosomatization in atopic dermatitis. OBJECTIVES: the objective of this study was to cross-culturally adapt and validate a Brazilian-Portuguese version of the Psychosomatic Scale for Atopic Dermatitis. METHODS: adaptation consisted of independent translation and backtranslation by three bilingual translators, followed by a pre-test. The Psychosomatic Scale for Atopic Dermatitis and the Dermatology Life Quality Index were self-administered to 47 patients with atopic dermatitis. Disease severity was evaluated using the Eczema Area and Severity Index. Factor analysis was used to identify the dimensions of the Brazilian Portuguese version of the Psychosomatic Scale for Atopic Dermatitis. Internal consistency and convergence validity were also analyzed. Reproducibility was assessed using the Kappa coefficient. RESULTS: factor analysis revealed a two-dimensional structure: stress/laziness/insecurity (I) and maladjustment/social relationships (II), explaining 54.4% of total variance. All dimensions revealed excellent internal consistency. External construct validity was confirmed by positive correlations between the Psychosomatic Scale for Atopic Dermatitis and the Dermatology Life Quality Index. Test-retest reliability was excellent, with k>0.7 for all questions. CONCLUSIONS: the Brazilian Portuguese version of the Psychosomatic Scale for Atopic Dermatitis demonstrated acceptable psychometric properties and can be used for the evaluation of psychosomatic symptoms in patients with atopic dermatitis and as a tool in clinical and epidemiological research.